(untitled) (Research, Society and Development, 2021)
The sertão tree tree is a tree species, present in several regions of Brazil, used especially in the Northeast for medicinal purposes. Diaspore seeds of species that develop in arid and semiarid regions, such as Caatinga species, are affected to situations inadequate for germination, such as high temperatures, high concentrations of soil sea and water deficiency. This work aimed to investigate the behavior of diaspores of Astronium urundeuva Fr. (M. Allemão) Engl. previously subjected to adverse conditions, aiming at a form of resilience of the species to such conditions. Some authors have proven improvements in seedling germination and vigor, when diaspores were submitted to physiological conditioning, both through hydration in water and osotic solutions, suggesting the hypothesis that diaspores conditioned and then exposed to abiotic stresses may have their quality recovered. There are few studies that point to conditioning as an attenuating technique of the effects caused by adverse conditions in diaspores of A. urundeuva, on the other hand, in some cases, it proves to be an excellent technique to increase the germinability and vigor of the species.